(3QSGFd COHjIs - (3eLghds
(3ChdgG (B:s
(3eDjO GdOhdI CWGd Gddg HbGDg s
(3BNQgG (B:s
(3eHJhQ BNQ GdehLhO efgG eGjfJgi CKfGA ecJhH ef GfTGA LGeY gPg GdQSGFd s
(3ChdgG QSGdJGf Edi eDjO GdOhdI GdYejO GdHhjgis
(3HChdgG agQS ef Yed eGdc GdeNWhWI hHBNQgG agQSs
(3JHUQI GdYfhGf (B:s
(3LeY s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdCOHs